Supporting research: new opportunities for 'subject librarians' and other staff - Brewerton, Antony (Henry Stewart Talks, 2012)
Warwick University Library and its development of community spaces, The learning grid, The teaching grid, The research exchange, Overview of changes in the teaching and learning environment, Overview of changes in the research environment, Overview of changes in the Library and Information Service business, A review of 'subject librarian' roles, The Research Libraries UK 'Subject Librarians' project, its aims and scope, The Research Libraries UK 'Subject Librarians' project, its findings, Supporting the 'research lifecycle', Skills sets required by subject librarians to support research and perception of needs, Further considerations in support research, Conclusions